Results from Two Scattered Light Photometers on Board an AFCRL Noctilucent Cloud Particle Collecting Payload. - Witt,Georg; Wilhelm,Nathan (1972)
A pair of scattered radiance polarization photometers were designed and built to supplement a noctilucent cloud (NLC) particle collecting experiment. The experiment was launched on August 8, 1970 in northern Sweden. The scientific background of the experiment is presented, and the technical design and calibration of the photometers is described. The basic theory, which relates the light scattering properties of NLC to the radiances measured by polarization photometers at two wavelengths, is also included.